Novel T3SS effector EseK in Edwardsiella piscicida is chaperoned by EscH and EscS to express virulence. (2nd November 2017) - Cao, Huifang; Yang, Cuiting; Quan, Shu; Hu, Tianjian; Zhang, Lingzhi; Zhang, Yuanxing; Yang, Dahai; Liu, Qin
Abstract: Bacterium usually utilises type III secretion systems (T3SS) to deliver effectors directly into host cells with the aids of chaperones. Hence, it is very important to identify bacterial T3SS effectors and chaperones for better understanding of host–pathogen interactions. Edwardsiella piscicida is an invasive enteric bacterium, which infects a wide range of hosts from fish to human. Given E. piscicida encodes a functional T3SS to promote infection, very few T3SS effectors and chaperones have been identified in this bacterium so far. Here, we reported that EseK is a new T3SS effector protein translocated by E. piscicida . Bioinformatic analysis indicated that escH and escS encode two putative class I T3SS chaperones. Further investigation indicated that EscH and EscS can enhance the secretion and translocation of EseK. EscH directly binds EseK through undetermined binding domains, whereas EscS binds EseK via its N‐terminal α‐helix. We also found that EseK has an N‐terminal chaperone‐binding domain, which binds EscH and EscS to form a ternary complex. Zebrafish infection experiments showed that EseK and its chaperones EscH and EscS are necessary for bacterial colonisation in zebrafish. This work identified a new T3SS effector, EseK, and its two T3SS chaperones, EscH and EscS, in E. piscicida, which enriches our knowledge of bacterial T3SS effector–chaperone interaction and contributes to our understanding of bacterial pathogenesis.